Recent Progress and Future Trends on State of Charge Estimation Methods to Improve Battery-Storage Efficiency : A Review - Qays, Md Ohirul; Buswig, Yonis.M.Yonis; Hossain, Md Liton; Ahmed, Abu-Siada (China electric power research institute, 2020)
Battery storage systems are subject to frequent charging/discharging cycles which reduce the operational life of the battery and reduce system reliability on the long run. As such, several Battery Management Systems (BMS) have been developed to maintain system reliability and extend the battery's operative life. Accurate estimation of the battery State of Charge (SOC) is a key challenge in the BMS due to its non-linear characteristics. This paper presents a comprehensive review on the most recent classifications and mathematical models of the SOC estimation. Future trends of the SOC estimation methods are also presented.